2018
DOI: 10.33225/pec/18.76.451
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of the Flipped Classroom: One Method, Many Intentions

Abstract: The Flipped Classroom is a teaching model where content attainment is shifted forward to outside of class, to be followed up by the teacher in class. In Sweden this way of teaching has become very popular during recent years. But what is gained by this way of teaching? Research on the Flipped Classroom in the context of the Swedish High School system is close to non-existent; why studies within this field are of great importance. In order to find appropriate informants, an electronic survey was constructed. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…), the management and collection of external resources, the assignment of different tasks, having the crucial feature of easy-to-use functionalities for online communication, discussion, cooperation, and feedback (Koch et al 2018). Besides facing operational difficulties in the application of these platforms of support in the flipped approach, another difficulty was demonstrated by Backlund and Hugo (2018); in their research in Sweden; they investigated the teachers' conceptions who develop and design pedagogical actions using the flipped approach. As a result, they revealed a diversity of concepts about who is being "inverted classroom."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), the management and collection of external resources, the assignment of different tasks, having the crucial feature of easy-to-use functionalities for online communication, discussion, cooperation, and feedback (Koch et al 2018). Besides facing operational difficulties in the application of these platforms of support in the flipped approach, another difficulty was demonstrated by Backlund and Hugo (2018); in their research in Sweden; they investigated the teachers' conceptions who develop and design pedagogical actions using the flipped approach. As a result, they revealed a diversity of concepts about who is being "inverted classroom."…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Hu (2018) clarified that unlike the previous teaching models, which focus on the content of the lecture given to students, the flipped classroom model emphasized the quality of learned content, how much the students have learned, and the strategies students apply to solve the problems themselves. Also, Backlund & Hugo (2018) added that the transition from traditional modes of teaching/learning toward applying the flipped classroom methodology had created numerous changes. The microlectures and teaching instructions had to be transformed into activities that occur outside of the class, which results in students' attendance in class time better prepared.…”
Section: Literature Review Flipped Learning and Teachingmentioning
confidence: 99%
“…A good general review of current flipped classroom research can be found in Bäcklund and Hugo (2018). In the following, we briefly touch upon the literature in the areas of the flipped university classroom as well as flipped high school and elementary school classrooms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A main finding in this practice was that the activity in class was more important than the details of the video. Bäcklund and Hugo (2018) interviewed Swedish upper secondary school teachers (not students) and found that research conducted on the Flipped Classroom in the context of the Swedish high school system is close to non-existent. Even when examining international literature on the Flipped Classroom .…”
Section: Flipped University Classroomsmentioning
confidence: 99%
See 1 more Smart Citation